2012
DOI: 10.1371/journal.pone.0050400
|View full text |Cite
|
Sign up to set email alerts
|

Ant Trail Pheromone Biosynthesis Is Triggered by a Neuropeptide Hormone

Abstract: Our understanding of insect chemical communication including pheromone identification, synthesis, and their role in behavior has advanced tremendously over the last half-century. However, endocrine regulation of pheromone biosynthesis has progressed slowly due to the complexity of direct and/or indirect hormonal activation of the biosynthetic cascades resulting in insect pheromones. Over 20 years ago, a neurohormone, pheromone biosynthesis activating neuropeptide (PBAN) was identified that stimulated sex phero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Mating generally causes changes in attractiveness, that is correlated with pheromone levels [40,41]. Many studies of lepidopteran species [42] and other insect orders [43,44] have shown that pheromone biosynthesis in females is stimulated by a brain factor known as pheromone biosynthesis-activating neuropeptide (PBAN). Therefore, we aimed to test whether a change in pheromone may result in mated females becoming less attractive by evaluating the mRNA expression of PBAN between mated female and virgin through quantitative real-time polymerase chain reaction (qRT-PCR) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Mating generally causes changes in attractiveness, that is correlated with pheromone levels [40,41]. Many studies of lepidopteran species [42] and other insect orders [43,44] have shown that pheromone biosynthesis in females is stimulated by a brain factor known as pheromone biosynthesis-activating neuropeptide (PBAN). Therefore, we aimed to test whether a change in pheromone may result in mated females becoming less attractive by evaluating the mRNA expression of PBAN between mated female and virgin through quantitative real-time polymerase chain reaction (qRT-PCR) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15][16] Pheromone biosynthesis in insects is controlled by distinct hormones, such as pheromone biosynthesis activating neuropeptide (PBAN), ecdysteroid, and juvenile hormone. [17] Hormonal regulation of pheromone biosynthesis in social hymenoptera remains poorly studied;h owever research on PBAN-regulated trail pheromone biosynthesis in fire ant Solenopsis invicta [18] andt he identification of PBAN [19] and ap utative gene homologue of PBAN-receptor in the honeybee Apis mellifera [20] indicatet hat PBAN might also play ar ole in the regulation of pheromone biosynthesis in social hymenoptera. It is thus acandidate hormone in MP regulation in bumblebees.…”
Section: Introductionmentioning
confidence: 99%
“…The PK subfamily peptides encoded from pyrokinin genes are conserved with a pentapeptide (FXPRLamide) at the C-terminal end that is diversified with WFGPRLamide in PK1 or DH, and with FXPRLamide in PK2 or PBAN (Jurenka, 2015). These peptides are involved in a variety of biological functions including the hindgut muscle contraction in the cockroach (Holman, Cook, & Nachman, 1986), sex pheromone biosynthesis in many moths (Raina et al, 1989), cuticle melanization in Leucuniu separutu (Matsumoto et al, 1990), induction of embryonic diapause in Bombyx mori (Imai et al, 1991), pupal development in Heliothis virescens (Xu & Denlinger, 2003), and trail pheromone production in Solenopsis invicta (Choi & Vander Meer, 2012).…”
mentioning
confidence: 99%